Synthesis of metal and semiconductor nanoparticles: progress towards understanding digestive ripening - Cingarapu, Sreeram (Kansas State University, 2010)
In recent years both metal and semiconductor nanoparticles have gained the attention of many research groups because of their unique properties. Synthesizing metal and semiconductor nanoparticles with narrow size distribution, uniform shape, and good crystalline nature represents a significant challenge. Our research group has taken the synthesis procedure a step forward when we discovered that “when a polydispersed colloidal solution upon heating at or near the boiling point of the solvent in presence of excess surface active ligands, the particles evolve into a thermodynamic equilibrium size regime and this phenomenon was named “Digestive Ripening”. The ability to tune the nanoparticles size with a narrow size distribution after post - preparation in a reproducible fashion is remarkable. The current dissertation research encompasses the field of metal and semiconductor nanoparticles and the major part of the work is devoted to understand the digestive ripening of gold-dodecanethiol system, and the effect of the nature of the ligand and solvent temperature on a low melting point indium metal – digestive ripening. A noteworthy achievement of the current work is the ability to extent the digestive ripening to the semiconductor materials cadmium selenide and cadmium telluride by employing different ligands and by the use of different solvents. A diverse set of instrumental techniques is used for the characterization of both metal and semiconductor nanoparticles.
Keywords: Metal and semiconductor nanoparticles; Digestive Ripening; Chemistry, Inorganic (0488)